A characterization of single‐peaked preferences via random social choice functions. Issue 2 (17th May 2016) - Chatterji, Shurojit; Sen, Arunava; Zeng, Huaxia
Abstract : This paper proves the following result: every path‐connected domain of preferences that admits a strategy‐proof, unanimous, tops‐only random social choice function satisfying a compromise property is single‐peaked. Conversely, every single‐peaked domain admits a random social choice function satisfying these properties. Single‐peakedness is defined with respect to arbitrary trees. The paper provides a justification of the salience of single‐peaked preferences and evidence in favor of the Gul conjecture ([Barberà, 2010] ).